Examining differential responses to the Take Care of Me trial: A latent class and moderation analysis. (December 2022) - Frohlich, Jona R.; Rapinda, Karli K.; Schaub, Michael P.; Wenger, Andreas; Baumgartner, Christian; Johnson, Edward A.; Blankers, Matthijs; Ebert, David D.; Hadjistavropoulos, Heather D.; Mackenzie, Corey S.; Wardell, Jeffrey D.; Edgerton, Jason D.; et al.
Highlights: Take Care of Me participants fell into three classes varying in risk. The low-risk class had the lowest pre-treatment symptom severity. The high-risk group had the highest symptom severity and executive dysfunction. Moderate risk individuals experienced the greatest benefits of the program. Future interventions may be tailored based on risk to maximize efficacy. Abstract: Given prevalent alcohol misuse-emotional comorbidities among young adults, we developed an internet-based integrated treatment called Take Care of Me . Although the treatment had an impact on several secondary outcomes, effects were not observed for the primary outcome. Therefore, the goal of the current study was to examine heterogeneity in treatment responses. The initial RCT randomized participants to either a treatment or psychoeducational control condition. We conducted an exploratory latent class analysis to distinguish individuals based on pre-treatment risk and then used moderated regressions to examine differential treatment responses based on class membership. We found evidence for three distinct groups. Most participants fell in the "low severity" group (n = 123), followed by the "moderate severity" group (n = 57) who had a higher likelihood of endorsing a previous mental health diagnosis and treatment and higher symptom severity than the low group. The "high severity" group (n = 42) endorsed a family history of alcoholism, and the highest symptom severity and executive dysfunction. Moderated regressions revealed significant class differences in treatment responses. In the treatment condition, high severity (relative to low) participants reported higher alcohol consumption and hazardous drinking and lower quality of life at follow-up, whereas moderate severity (relative to low) individuals had lower alcohol consumption at follow-up, and lower hazardous drinking at end-of-treatment. No class differences were found for participants in the control group. Higher risk individuals in the treatment condition had poorer responses to the program. Tailoring interventions to severity may be important to examine in future research.